Influence the loading conditions and the stress concentrators on the spatial-time inhomogeneity due to the yield delay and the jerky flow: study by using the digital image correlation and the infrared analysis - Tatyana V. Tretyakova; Valery E. Wildemann (Fracture and Structural Integrity)
The paper deals with the investigation of the temporal instabilities and spatial localization due to the Lders behavior and the PortevinLe Chatelier effect in the carbon steel C1010 and the aluminummagnesium alloy AA5052, which manifest the unstable plastic flow. The digital image correlation technique and the infrared thermography were used to capture and study the processes of the initiation and propagation of the deformation bands. The main part of the research focuses on the estimation of the influence of the loading systems stiffness on the irregular plastic flow, which was carried out on flat specimens with complicated geometry and on specimens with additional deformable parts